Unusual localization and aggressive progression of large infantile fibrosarcoma - İsmail Burak Atalay; Guray Togral (Acta Orthopaedica et Traumatologica Turcica, 2019)
Infantile fibrosarcoma is a very rare soft tissue tumor in infants and children most commonly located in extremities. It constitutes less then 1 percent of all childhood cancers. Prognosis and clinical course of it is relatively good compared to adult forms. Local recurrence is common but metastasis is infrequent.In this case report we present infantile fibrosarcoma with relapse and lung metastasis despite neoadjuvant chemotherapy, pelvic reconstruction surgery with wide surgical excision and adjuvant chemotherapy protocol. The patient was a 2-year-old girl at the time of diagnosis, and there was a huge mass in pelvic region. After neoadjuvant chemotherapy, type 1 pelvic resection and pelvic reconstruction with bone cement performed. The patient presented with relapse and lung metastasis 6 months after the surgery.This is the first report of pelvic infantile fibrosarcoma with pelvic resection surgery. This case suggests that these tumors may exhibit unpredictable clinical behavior. Keywords: Infantile fibrosarcoma, Pelvic region, Distant metastasis, Surgical treatment, Chemotherapy